Analisis Tindak Tutur Lokusi Dan Ilokusi Dalam Acara “Lapor Pak” Episode “Introgasi Ganjar Pranowo” Sebagai Kajian Pragmatik - Mellyana Dwi Utami; Laksa Rizal Putra Wahyudi; Niska Arda; Masitha Hamida; Muhammad Yahya Atsaqof; Eni Nurhayati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
The study aims to explain forms of speech and hypnosis in a TV show "reports Sir! An episode of "ganjar pranowo" interrogation. The research method used in this study is a qualitative type of descriptive method. Data was generated via both the speech of the lokusi and the illegation described by the players. The research data source is a sentence or a dialogue told by a TV performer. The data-gathering techniques of this research are using wiretapping techniques. The study obtained as many as 5 known force-of-speech data and 3 self-contained, reflective, commissar, expressive, and declarative ative data of the study. Researchers have concluded that the most powerful types of speech speech have occurred in the study as types of expressive speech.